Halftone image compression based on probabilistic run length encoding - H. K. Al-Bahadily; V. Yu. Tsviatkou; V. K. Kanapelka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
There are proposed run-length encoding algorithms to compress grayscale images lossless and loosy compression taking into account the likelihood of the occurrence of pixel values and providing thereby increasing the compression ratio.